Antiviral strategies targeting herpesviruses - Haisi Dong; Zeyu Wang; Daqing Zhao; Xiangyang Leng; Yicheng Zhao (Elsevier, 2021)
Herpesviruses, known as large DNA viruses, have a wide host range. In addition to human beings, cattle, and horses, even carp can be hosts for herpesvirus infection. Herpesviruses are pathogens possessing elaborate mechanisms that regulate host cell components for its replication, assembly and generating mature virus particles that can infect humans and most animals, usually causing multiple and lifelong infections. In addition, several human diseases, such as genital or mouth herpes, mononucleosis, and Burkitt lymphoma, are usually associated with herpesvirus infection. Blocking the steps of viral infection, such as entry, replication and assembly, may be an effective way for many different herpes viruses and their related diseases. Therefore, we aim to describe antiviral agents that are able to prevent herpesvirus entry, replication and assembly in host cells. We summarize antiviral strategies, including certain small molecular drugs, RNA interference and CRISPR/Cas9 system-based antiviral approaches, which represent promising approaches.